Divorcio en España entre cónyuges marroquíes: la Sentencia de la Audiencia Provincial de Barcelona de 30 diciembre 2014 - Carrillo Lerma, Celia (CUADERNOS DE DERECHO TRANSNACIONAL, 2015)
La Audiencia Provincial de Barcelona, Sección 12ª, en Sentencia nº 830/2014, de 30 diciembre 2014, aplica el artículo 22.3º LOPJ para fundar la competencia judicial internacional de los tribunales españoles para conocer sobre un divorcio entre cónyuges marroquíes residentes en España, lo cual es erróneo porque el Reglamento (CE) 2201/2003, de 27 de noviembre, resulta aplicable. De otro lado, aplica correctamente el artículo 107.2º CC para determinar la Ley reguladora del divorcio, puesto que, a fecha de presentación de la demanda, el Reglamento (UE) 1259/2010, de 20 de diciembre, aún no era aplicable. Palabras clave: divorcio, cónyuges marroquíes, competencia judicial internacional, Ley aplicable. Abstract: The Provincial Court of Barcelona, Section 12th, in Decision No. 830/2014 of 30 December 2014 applies the Article 22.3 LOPJ to base on the international jurisdiction of the Spanish courts in order to seise of a divorce among a Moroccan couple who is habitually resident in Spain, which is wrongful since the Council Regulation (EC) No. 2201/2003 of 27 November 2003 is applicable. Moreover, it correctly applies the Article 107.2 CC to determine the law applicable to divorce, given that the Council Regulation (EU) No. 1259/2010 of 20 December 2010 was not applicable at the time of the divorce application was introduced Key words: divorce, Moroccan couple, international jurisdiction, choice of law.